Phytochemicals constituents, antioxidant activities and cytotoxicity assays of few wild edible fruits of North-East India - Tridip Kumar Hazarika; Lalnunpuia Varte; Vabeiryureilai Mathipi; Lalrinzuali Khawlhring; Esther Lalruatsangi; Panthor Debbarma; Nachimuthu Senthil Kumar (International Journal of Food Properties, 2023)
Wild edible fruits are found globally and play multifarious functions. The present study was undertaken to study the antioxidants and anti-cancerous potential of six wild edible fruits from Mizoram viz. Garcinia lanceifolia, Embelia subcoriacea, Elaeocarpus tectorius, Elaeagnus caudata, Cissus obovata and Averrhoa carambola. The fruits were identified through ITS1 and ITS2 partial genes and the sequences were submitted to GenBank depository and NCBI databases. Physical and physico-chemical characteristics were assessed for their importance. The phytochemical content of the fruits was analyzed qualitatively and shown the presence of saponin, flavonoids, tannin, cardiac glycosides, alkaloids and terpenoids. The extracts were then subjected to quantification of secondary metabolites, such as gallic acid, rutin and quercetin. Further, secondary metabolites, such as gallic acid, rutin, quercetin, hesperidin and naringin were quantified by the HPLC method, which showed significantly high quantity from the extracts. The free radical scavenging activity performed using DPPH and ABTS cations revealed that the extracts possess high potency for scavenging properties, with IC50 ranging from 10.37 to 567.8 µg ml−1. The cytotoxicity of the extracts assessed against A549 cancer cell line showed potency, with IC50 value ranging from 18.2 to 203.2 µg ml−1. Therefore, the present study revealed that wild edible fruits could be a good resource for ethno-medicine as well as income generation for the local people of Mizoram, north-east India.